2019
DOI: 10.32642/wijas.v1i0.1361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Musca domestica (House fly) larvae production from organic waste

Abstract: The objective of the study was to investigate the effect of organic waste (pig manure and chicken layer droppings) on the production of house fly larvae (HFL) and its nutritive value. A completely randomised design was used, with three treatments (pig manure, chicken layer dropping and equal combination of the pig and chicken excreta) replicated six times. The data for biomass reduction, larvae wet and dry weight, moisture, ash, crude fibre, crude protein, fat, calcium and phosphorus were analysed using analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Westwood (Cirina forda) [25] The ability of broiler chicks to replace FM (30,50,70, and 100%) with Cirina forda larvae was tested. The findings demonstrated that the FI and BWG of birds given larvae-containing diets did not differ substantially from the CG during the starter and finisher stages.…”
Section: Crickets (Gryllus Testaceus Walker)mentioning
confidence: 99%
“…Westwood (Cirina forda) [25] The ability of broiler chicks to replace FM (30,50,70, and 100%) with Cirina forda larvae was tested. The findings demonstrated that the FI and BWG of birds given larvae-containing diets did not differ substantially from the CG during the starter and finisher stages.…”
Section: Crickets (Gryllus Testaceus Walker)mentioning
confidence: 99%
“…The housefly (Musca domestica) is considered a cosmopolitan insect species (Ortiz et al, 2011), having a high capacity to adapt to the environmental changes caused by man (Britto et al, 2008). Housefly larvae, in addition to having a high content of crude protein and ether extract (Table 5), also bring the benefit of reducing the organic matter used in their rearing (in the order of 40-50%), facilitating and potentiating their use as agricultural fertilizers (Uushona, Simasiku, & Petrus, 2019). Housefly meal (HFM) has great potential as a possible sustainable protein source and alternative in diets for poultry farming, providing animals with a large amount of energy and proteins, having a profile of essential amino acids that meets the nutritional requirements of birds (Pieterse & Pretorius, 2014), in particular, higher amounts of lysine, threonine and methionine compared to plant-based sources (Khan et al, 2016;Gadzama & Ndudim, 2019).…”
Section: Housefly (Musca Domestica) Larvae Mealmentioning
confidence: 99%
“…SD: standard deviation; N: number of studies observed; DM: dry matter; Source: 1(Adeniji, 2007;Pieterse & Pretorius, 2014;Khan et al, 2016;Uushona et al, 2019).…”
mentioning
confidence: 99%